O trabalho docente como determinante de qualidade em educação: um estudo de caso em uma IES privada do município de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2007)
The higher education in Brazil is facing a serious moment due to the fact that the number of private Higher Educational Institutions is increasing fast lately. Because of that, the education quality in those institutions has got deeply degraded, which is producing dissatisfaction of the whole academic body and, also, the market. Having that in mind, this study states the professor’s work that can determine the quality of the education in a private higher institution and it aims at analyzing the possible quality indicators in the teachinglearning process. The methodological procedures used were simultaneously the bibliographic research and the descriptive research, being chosen the case study technique. The results pointed to a higher education that is facing a period of transition due to the fact that a percentage of the professors have not realized to the need of the constructive capacity as one of the quality indicator in the Higher Education.
Keywords: Educação Superior; Qualidade do ensino; Trabalho Docente; Indicadores de qualidade; ENGENHARIAS: ENGENHARIA DE PRODUÇÃO